COMPUTER SCIENCE IN THE EDUCATION OF UKRAINE: FORMATION PROSPECTS - Viktor Shakotko (Kherson State University, 2016)
The article deals with the formation of computer science as science and school subject as well in the system of education in Ukraine taking into consideration the development tendencies of this science in the world. The introduction of the notion« information technology», «computer science» and «informatics science» into the science, their correlation and the peculiarities of subject sphere determination are analyzed through the historical aspect. The author considers the points of view concerning determination morphology basis of computer science, its aims and content. A comparative analysis of school and higher educational establishment computer science content since the beginning of introduction this subject into the curriculum till nowadays is conducted. The author examines the recommendations of the International communities ( UNESCO International Congress «Education and computer science» (Moscow, 1996) , Computer science Principles International Conference FIS (Beijing, 2010), International Summit ISSI « Information society at the cross-roads » (Vienna,2015 ))concerning aims and the computer science content in the educational systems of different countries and analyzes world tendencies reflection towards content of computer science teacher training at the Ukrainian higher educational establishments . The necessity of inserting amendments into the structure of academic discipline «computer science» at the higher educational establishments is substantiated